Pengaruh Ragam Kecerdasan dan Motivasi terhadap Kinerja Guru Sekolah Menengah Atas (Studi Deskriptif tentang Guru SMAN pada Dinas Pendidikan Kota Jayapura-Papua) - Khairuddin NM; Djumilah Zain; Armanu Thoyib; Mintarti Rahayu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
The main problem of this research is the influence of various intelligence and motivation to Senior High School teachers’ performance at Jayapura Municipality. The objective of this research is to reveal empirically the influence of intellectual, emotional and spiritual intelligence, extrinsic and intrinsic motivation to the Senior High School teachers’ performance at Jayapura city/municipality. This research uses quantitative method and supported by qualitative method (mixed method). The total of the population of this research is 225 teachers. From these populations there 114 teachers are taken as samples by using systematic sampling technique. Technique of collecting data conducted by RPM intelligence test, questionnaire EQ, SQ, extrinsic motivation, intrinsic motivation, and APKG questionnaire (Teacher Performance Appraisal Instrument). All sorts of these questionnaires refer to Likert scale. Before administering this questionnaire, it has been conducted try out on 40 teachers to see its reliability and its validity. Data analysis uses multiple regression analysis technique and qualitative analysis. The findings of this research indicate influence among intellectual intelligence, emotional intelligence, spiritual intelligence, extrinsic motivation and intrinsic motivation to teachers’ performance positively and significantly. It means that the higher the intellectual intelligence, emotional intelligence, spiritual intelligence, extrinsic motivation and intrinsic motivation the higher their influence on performance. The three kinds of intelligences and two kinds of motivation variables of this research has given various contributions on performance. Among the five variables of this research, extrinsic motivation has the most dominant influence toward performance. In terms of intelligence variables, the intellectual intelligence has more dominant influence towards performance if it is compared with emotional intelligence and spiritual intelligence. It is also found that extrinsic motivation has contributed more dominantly than intrinsic motivation. Based on the findings of this research, it is recommended to the National Education Department and Head of Senior High School in Jayapura city that they should perform various actions, such as 1) the creation of a conducive working environment for expressing and growing potency to both kinds of intelligence and both teacher’s intellectuals, emotional and spiritual intelligences, 2) should be created working atmosphere than can motivate teachers to work both intrinsically and extrinsically to further improvement of teachers’ performance.Keywords: Intellectual intelligence (IQ), emotional intelligence (EQ), spiritual intelligence (SQ), extrinsic motivation, intrinsic motivation, and performance.